Effect of seed enhancement treatments and plant spacing on the field performance of hybrid cotton - MENKA; SHIV K. YADAV; JAGMAIL SINGH; ELDHO VERGHESE (Seed Research, 2026)
Seed enhancement is a widely used technique to improve field emergence, uniformity and final plant establishment under wide range of environmental conditions. Field experiments were conducted during kharif 2010 and 2011 to find out effective seed enhancement treatment and suitable spacing for Bt Express and non Bt Express cotton hybrids. A total of 17 seed quality enhancement treatments were attempted for enhancing the field performance of cotton hybrids. Significantly higher field emergence and final plant stand establishment were observed in the seeds treated with azotobacter + microphos (10g each/kg of seed) followed by thiram+ imidacloprid (2.0 g/kg seed + 7.5ml/kg seed) treatment. These two treatments also resulted in early initiation of flowering, 50% flowering and 50% boll opening over all other treatments. Therefore, these presowing seed treatments are recommended before sowing in the field. Among the three, spacing of 75×60cm was found to be significantly superior over 75×75cm and 75×30cm, thus it may be followed to obtain their better field performance.